Dampak Lingkungan Kerja Fisik dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Karyawan - Herman Surijadi; Yuslan Idris (Univiversitas Dr. Djar Wattiheluw, 2020)
The aim of this study is to examine and analyze the effect of physical and non-physical working environment on the employee working satisfaction. The population in this study are all employees of Matahari Department store in Ambon City Center (ACC) in Ambon. The sampling technique used in this study is census technique with 79 respondents as final amount of sample. Data collection in this study is taken using questionnaire, while the analysis of the data to answer the research question used multiple linier Regression analysis. The result shows that the physical and non-physical working environment proven to have positive and significant impact on the employees working satisfaction in Matahari Department store in Ambon City Center (ACC) in Ambon City. This is shown by regression coefision of physical and non-physical working environment in which if they increase, it is followed by the increase of employees working satisfaction. Thus, it can be said that the increase of physical and non-physical working environment value will increase the employees working satisfaction in Matahari Department store in Ambon City Center in Ambon.